1957
DOI: 10.2134/agronj1957.00021962004900080010x
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Birdsfoot Trefoil‐Bluegrass and Ladino Clover‐Bluegrass for Pasture: I. Response of Lambs1

Abstract: Synopsis During the first grazing year, a Ladino clover‐bluegrass mixture was more productive in terms of carrying capacity, gain per acre, and TDN consumption per acre than an Italian birdsfoot trefoil‐bluegrass mixture. The trefoil mixture was more productive the remaining two years of the test. Ladino clover was eliminated from the mixture by drouth. Continuous grazing killed the birdsfoot trefoil. The trefoil remained in the mixture when grazed with a rotation system of about two weeks grazing and four wee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
1

Year Published

1958
1958
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 1 publication
0
7
1
Order By: Relevance
“…The yield of dry herbage from the pastures as measured by caged samples is shown in table 1. Neither the apparent higher yield of the trefoil mixture nor the higher yield of the continuously grazed pastures in 1953 agree with animal response data reported in an earlier paper ( 4 . .…”
Section: Resultscontrasting
confidence: 62%
See 1 more Smart Citation
“…The yield of dry herbage from the pastures as measured by caged samples is shown in table 1. Neither the apparent higher yield of the trefoil mixture nor the higher yield of the continuously grazed pastures in 1953 agree with animal response data reported in an earlier paper ( 4 . .…”
Section: Resultscontrasting
confidence: 62%
“…Numerous methods of measuring productivity without the use of grazing animals have been investigated. In an earlier paper the authors ( 4) reported animal response from grazing birdsfoot trefoil-• bluegra~:s and Ladino clover-bluegrass pastures. Samples from caged areas and from grazed areas were taken during the course of the experiment.…”
mentioning
confidence: 99%
“…The superiority of birdsfoot trefoil to Ladino clover under drouthy conditions has also been shown in grazing trials with lambs by Davis and Bell (2) in Ohio. They reported that Ladino clover was practically eliminated by drouth in the second year of the experiment.…”
mentioning
confidence: 74%
“…Most of the work undertaken in the United States on grass-legume mixtures has been with white clover (Trifolium repens L.) and trefoil (Lotus spp.) with various grasses, e.g., Austenson and Law, (1955) and Davis and Bell, (1957). A number of studies on subcloverperennial grass management have been made in Australia.…”
Section: Introductionmentioning
confidence: 99%